BRAND EXPERIENCE DAN SOCIAL MEDIA MARKETING : KUNCI PEMBELIAN PRODUK KECANTIKAN SHOPEE - Rizky Maulana; Eva Fathussya Adah; Noornissa Sarah Ginanjar (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to analyze the influence of Brand Experience and Social Media Marketing on purchasing decisions for beauty products among Shopee e-commerce users in Sukabumi. The research method used is quantitative with an associative approach. The sample consists of 96 respondents, determined using Cochran's formula. Data were collected through a questionnaire. Data analysis was conducted using multiple linear regression, t-test (partial), and F-test (simultaneous), with the assistance of SPSS. The results show that Brand Experience (X1) has a positive and significant partial effect on purchasing decisions (Y) for beauty products on Shopee in Sukabumi (t-value 5.386 > t-table 1.986; sig. 0.000 < 0.05). Social Media Marketing (X2) also has a positive and significant partial effect on purchasing decisions (t-value 5.234 > t-table 1.986; sig. 0.000 < 0.05). Simultaneously, Brand Experience and Social Media Marketing have a significant influence on purchasing decisions (F-value 604.194 > F-table 3.09; sig. 0.000 < 0.05). The Adjusted R Square value of 0.927 indicates that 92.7% of the variation in purchasing decisions can be explained by the two independent variables. In conclusion, Brand Experience and Social Media Marketing are significant key factors influencing purchasing decisions for beauty products on Shopee in Sukabumi.